THE EFFECT OF ORGANIZATIONAL RULES, WORK ENVIRONMENT WITH WORK SATISFACTION AS A VARIABLE INTERVENING TO THE PERFORMANCE OF HIGH SCHOOL TEACHERS IN BATAM - Manalu, Nelly Chandrawati (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the relationship of organizational role, and work environment to teacher performance with job satisfaction as mediation variabel in high school Batam City in Indonesia Kepulauan Riau Province. The design used is hypothesis testing using Structural Equation Modeling (SEM) because the variables used in this study use mediating variables. The population and respondents in this study was teacher senior high school (SMA) in Batam city. The results testing of the study show that the organizational roles has no significant effect on teacher performance with P Value = 0.582 and work environment also has no significant affect to teacher performance with P Value = 0,836 directly between organization roles and work environment has no significant effect on teacher performance. Organization roles and work environment has significant effect on work satisfaction with P Value < 0, 05. The results also show that work satisfaction mediates the organizational roles of teacher performance and work satisfaction is mediation between work environments on teacher performance. Based on the two tests above between the mediation test and the direct test, it can be concluded that the rules of the organization do not have a significant impact on the performance of teachers for that the schools, management and education offices focus on teacher job satisfaction itself to improve teacher performance, and so do the the work environment is not a variable that directly has a significant impact on teacher performance but the work environment has a direct effect on job satisfaction, in other words job satisfaction is also proven to contribute to improving and providing a significant effect as a mediator on the performance of high school teachers in Batam. Future research model can explain the role of organizational commitment in organizational structure, organizational strategy and management changes to school performance and increase the teacher performance in senior high school (SMA) in Batam.